Pengaruh Profitabilitas, Likuiditas, Solvabilitas, Dan Aktivitas Terhadap Nilai Perusahaan: Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Food & beverage yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Reviani, Dea Riska; Hakim, Astrid Dita Meirina (CV. ULIL ALBAB CORP, 2024)
This study aims to determine the influence of Profitability, Liquidity, Solvency, and Activity partially on Company Value in the food & beverage sub-sector listed on the Indonesia Stock Exchange for the 2019-2023 period. The population of this study is 95 companies in the food & beverage sub-sector listed on the Indonesia Stock Exchange for the 2019-2023 period. The determination of the sample in this study used purposive sampling and the sample used was 38 companies in the food & beverage sub-sector listed on the Indonesia Stock Exchange for the 2019-2023 period. This study uses a panel data regression statistical analysis tool assisted by the Eviews version 12 program and Microsoft Excel 2016. The results of the study show that Profitability partially affects and significantly affects the Company's Value. Meanwhile, Liquidity, Solvency, and Activity partially have no effect on the Company's Value